Influence of food availability on the diet and activity budget of two western lowland gorilla (Gorilla gorilla gorilla) groups of differing size in the Dzanga-Ndoki National Park, Central African Republic - Terence Fuh Neba; Giuseppe Donati; Angelique Todd; Shelly Masi (Revue de Primatologie)
Variation in food availability, body size and group size are known to influence primate diet and activity budgets. Here we report how seasonal food availability shapes the diet and activity patterns of two habituated western lowland gorilla (WLG) groups of differing size. WLGs are ripe fruit opportunists, showing dietary flexibility when preferred foods are scarce. However, as fruit can be rare/ patchily distributed, as intra-group feeding competition increases with group size, access to individual patches may be limited. We thus predicted that frugivory decreases with increased group size and influences diet and activity budgets accordingly (increased diet breadth and time feeding since relying on alternative/lower quality food). First, we compared food availability between home-ranges by monitoring leafing/fruiting patterns of major gorilla food trees. Second, we compared the groups’ activity budgets and diet composition/diversity, testing for differences between high (HF) and low fruit seasons (LF). We measured gorilla activity over six months by continuous focal sampling of 16 target animals rotated daily from both groups (N=9 and N=15). Our results confirm that WLG diet consisted mainly of fruits (36%, then: stems 24%; leaves 21%; insects 14%; other food types 3%, and bark 2%) and spend most of their time feeding (39%, then: resting 33%; traveling 19%; social 5%, and other activities 4%). However, contrary to our predictions, we found no group differences within or between seasons: irrespective of group size both spent significantly less time feeding, but more time traveling and socializing, and consumed significantly more fruits, less leaves and bark during the HF compared to the LF. Our results show that WLG activity budgets and diet appear to vary more in response to ripe fruit availability than group size. We suggest that WLGs may cope with increased group size costs through other mechanisms such as group spread, rather than lowering diet quality or further changing activity patterns. Such flexibility may better allow WLG groups to track ripe fruits when available but, unlike sympatric chimpanzees, switch to more herbivorous diets when necessary, adjusting activity budgets accordingly ; WLGs thus may be considered more resilient faced with environmental change such as forest degradation.